Cognitive Reserve and the course of Alzheimer's disease. - Sobral, M.; Pestana, M.H.; Paúl, C. (ICAP14_ABS4059 - no prelo, 2013)
Alzheimer´s Disease (AD) is the most common form of dementia in the elderly and Cognitive Reserve (CR) describes the capacity of the adult brain to tolerate the effects of this neurodegenerative process and to minimize the clinical manifestation of pathology of dementia. The aim of this work was to evaluate the association of Cognitive Reserve and the course of Alzheimer´s disease. Methods: Functional and neuropsychological abilities of 75 outpatients with probable AD diagnosis were evaluated. Data collected included socio-demographic and clinical variables. Patients completed two questionnaires, "Participation in leisure activities throughout life” and Cognitive Reserve Questionnaire. Patients were administered the Mini-Mental State Examination, Addenbrooke´s Cognitive Examination Revised, Clinical Dementia Rating, tests adapted from the Lisbon Battery for Assessment of Dementia and the Barthel Index and the Lawton and Brody’s Index. Results: The relationship between the CR (evaluated with the Cognitive Reserve Questionnaire) and the years of evolution of dementia showed no statistically significant differences. Patients with more than five years of education, greater participation in leisure activities and more differentiated profession had a slower progression of the disease than other patients with less education, lower participation in leisure activities and less differentiated profession. Conclusion: AD patients with high CR may benefit from a slower cognitive decline after diagnosis of AD.